2022
DOI: 10.3390/ijms23031534
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Products of Photooxidative Destruction of the Bisretinoid A2E Cause Proteins Modification in the Dark

Abstract: Aging of the retina is accompanied by a sharp increase in the content of lipofuscin granules and bisretinoid A2E in the cells of the retinal pigment epithelium (RPE) of the human eye. It is known that A2E can have a toxic effect on RPE cells. However, the specific mechanisms of the toxic effect of A2E are poorly understood. We investigated the effect of the products of photooxidative destruction of A2E on the modification of bovine serum albumin (BSA) and hemoglobin from bovine erythrocytes. A2E was irradiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 66 publications
1
11
0
2
Order By: Relevance
“…Thus, the greatest cytotoxicity in relation to RPE cells was shown by lipofuscin-fed RPE samples maintained in the dark after irradiation. These results support our assumption [ 38 , 41 ] that BisRets-OX with hydrophilic and amphiphilic features can have cytotoxic effects on RPE cells. The results of our experiments correlate with the other literature data [ 47 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Thus, the greatest cytotoxicity in relation to RPE cells was shown by lipofuscin-fed RPE samples maintained in the dark after irradiation. These results support our assumption [ 38 , 41 ] that BisRets-OX with hydrophilic and amphiphilic features can have cytotoxic effects on RPE cells. The results of our experiments correlate with the other literature data [ 47 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 91%
“…In earlier in vitro experiments [ 38 ], we demonstrated that BisRets-OX, which are formed when LGs are irradiated with visible light, have both hydrophilic and amphiphilic properties, allowing their diffusion through the LG membrane into the RPE cell cytoplasm. It was established that these products contain cytotoxic carbonyls, which can modify cellular proteins and lipids [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations